PERAN STRATEGIS PENDIDIKAN ISLAM DI ERA GLOBALISASI - Arif Shaifudin (Al Hikmah: Jurnal Studi Keislaman, 2016)
In the middle of the swift currents of globalization, education as fertile ground in contributing to the culture of various nations around the world. The loss of a divider between countries create contiguity between nations values was inevitable. In such circumstances, the identity of a nation semakinn difficult to maintain that tend to be difficult to recognize a characteristic of a nation, not a nation terkeculai Indonesia. Indonesia with the majority of the population who Bergama Islam as also experienced a cultural shift with globalization in various lines today. Islamic education which has long provided a color for the national identity seemed to lose the trust of the community and make the products of Western culture as an example of progress is desirable. This is where Islamic education should take back its role in maintaining the ideal figure of an intelligent human being spiritual, intellectual, and social activities. Islamic education should be able to sensitize the public that Islam does not want the people of the backward, ignorant, and do not respond to the times. On the contrary, Islam through education is very much attention to the progress of mankind. Even the promise of Islamic education in various fields of holistic establishment framed in values to Islamization.